Storying violence : unravelling colonial narratives In the Stanley trial - Starblanket, Gina; Hunt, Dallas (Toronto : Arbeiter Ring Publishing, 2020)
In August of 2016, Cree youth Colten Boushie was shot dead by Saskatchewan farmer Gerald Stanley. Using colonial and socio-political narratives that underlie white rural settler life, the authors position the death of Boushie and trial of Stanley in relation to Indigenous histories and experiences in Saskatchewan. They point to the Stanley case as just one instance of Indigenous peoples' presence being seen as a threat to settler colonial security, then used to sanction the exclusion, violent treatment, and death of Indigenous peoples and communities.
Chapter 1 -- Storying the prairie west -- Chapter 2 -- The case that's "not about race" -- Chapter 3 -- Whites "coveted Indian land but not land with Indians on it" -- Chapter 4 -- "Settler reason" and the unheard -- Conclusion: where to from here?
Includes bibliographic references and biographies.
Native American and Indigenous Studies Association (NAISA), Best Subsequent Book, 2021.
eBooks on EBSCOhost
Keywords: Stanley, Gerald -- (Farmer) -- Trials, litigation, etc; Boushie, Colten; Trials (Murder) -- Saskatchewan; Trials (Manslaughter) -- Saskatchewan; Indigenous peoples -- Violence against -- Saskatchewan; Saskatchewan -- Race relations; Saskatchewan -- Ethnic relations; Procès (Meurtre) -- Saskatchewan; Procès (Homicide involontaire) -- Saskatchewan; Ethnic relations; Indigenous peoples -- Violence against; Race relations; Trials (Manslaughter); Trials (Murder); Saskatchewan; Trials, litigation, etc